Peace by Peaceful Means? A Preliminary Examination of Buddhist Peacebuilding in Post-Conflict Nepal - King, Anna (Religions of South Asia, 2015)
This article reflects the growing interest of governments, international development, peace and interfaith organizations, and academics in the link between religions and conflict, and in the fact that religion often serves as a vehicle and language for protest and conflict. It is often deeply implicated in national, ethnic, cultural, and/or geopolitical considerations. The article also reflects the fact that religious studies as a discipline is increasingly required to demonstrate public relevance and impact in debates concerning the role of religion in conflict and conflict transformation. It grows out of a research project which explores the potentially constructive role of religions in active peacebuilding, postconflict reconciliation and restorative justice while acknowledging that there are multiple interpretations of religious traditions that can relate to militancy, chauvinism and nationalist ideologies. The project is focused on post-conflict Nepal, and works horizontally and vertically with grassroots and local organizations as well as with transnational institutions and international bodies. This article is a preliminary contextualization of one strand of the project, Buddhist contributions to the peace-building and post-conflict recovery. It draws a broad picture of the ways in which Buddhism has been constructed politically as a universalist culture of peace, but is also associated with competing ethnic identities and ‘nationalities’. It considers how far Buddhist organizations, communities and leaders have been able to engage with the immediate causes of the civil war (1996–2006), and the deep structural issues, inequalities and injustices which drive grievance and violence.